The Effect of Cognitive Behavior Theraphy On Online Gaming Addiction In Adolescents - Indah Andriani Ansar; Fatmawati; Haerati (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2021)
Adolescence is one of the transitional periods of human development, where a person cannot be called an adult but no longer a child. The biggest users of online games in Indonesia are teenagers, where for teenagers playing online games is not a strange thing. pleasure and fun when playing games causes feelings of helplessness or inability to stop playing online games, so that in the end it affects other activities that are usually done daily. Knowing the effect of cognitive behavior therapy on online game addiction in adolescents at SMAN 7 Bulukumba in 2020